Sensorless control of PMSM for low speed range. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski; Krzysztof Zawirski, Andrzej; Urbanski, Konrad
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop the Permanent Magnet Synchronous Motors drive which has possibility to work in sensorless mode at low speed based on back EMFs estimation. Design/methodology/approach – Estimation uses modified Luenberger observer and the preprocessing of the EMFs before calculating the speed, using derivative and the Kalman filter (KF) to obtain smooth waveform of the estimated speed. This modification is needed because of the nonlinear change of the estimated back EMFs amplitude as a function of speed, in low-speed range. Findings – How to use back EMF observer to estimate a speed in the low-speed range was found in the course of the work. Simple and effective algorithm uses KF and can work even with a relatively big deformation of the estimated back EMF. Practical implications – Such sensorless drive may be used in low-cost constant or variable speed drive in domestic use or industrial application. Such drive may work properly where there is no initial load torque and the sign of the speed does not change. Originality/value – Presented results challenge the view that at low-speed range (not the standstill), the back EMF-based method of position estimation is very difficult or impossible. However, the problem lays in proper speed estimation, not the position estimation.